2015
DOI: 10.1080/00332747.2015.1069658
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-Inducing Media: The Effect of Constant News Broadcasting on the Well-Being of Israeli Television Viewers

Abstract: Increased viewing patterns of televised traumatic content, as well as negative perception of such broadcasts, are associated with the report of anxiety symptoms or psychopathology. The public health implications of the findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 24 publications
2
48
1
2
Order By: Relevance
“…The lack of such research is surprising, as media exposure is typically detrimental, even when people were only exposed to the media coverage of terrorism but were not exposed to an actual terror incident at all. In such cases, media exposure alone was associated with increased PTSD symptom levels (Holman, Garfin, & Silver, ) or increased anxiety (Bodas et al, ). In addition to the above, the current study examined additional correlates of ISIS anxiety to gain better insight into the ISIS anxiety profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of such research is surprising, as media exposure is typically detrimental, even when people were only exposed to the media coverage of terrorism but were not exposed to an actual terror incident at all. In such cases, media exposure alone was associated with increased PTSD symptom levels (Holman, Garfin, & Silver, ) or increased anxiety (Bodas et al, ). In addition to the above, the current study examined additional correlates of ISIS anxiety to gain better insight into the ISIS anxiety profile.…”
Section: Discussionmentioning
confidence: 99%
“…ISIS media is neither banned by governments nor is its viewing discouraged by mental health professionals. Although research from other contexts suggest that media exposure both to natural disasters (Goodwin, Palgi, Hamama-Raz, & Ben-Ezra, 2013;Goodwin, Palgi, Lavenda, Hamama-Raz, & Ben-Ezra, 2015), as well as to terrorist attacks (Ahern et al, 2002;Bodas et al, 2015;Pfefferbaum et al, 2000), may have deleterious effects, at least in the short term (Neria & Sullivan, 2011), exposure to ISIS media was not studied. The lack of such research is surprising, as media exposure is typically detrimental, even when people were only exposed to the media coverage of terrorism but were not exposed to an actual terror incident at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research findings are not all in agreement on the issue of whether or not exposure to constant media coverage of fearful and traumatic events may cause full-fledged PTSD (Bodas, Siman-Tov, Peleg, & Solomon, 2015). Some researchers indicate findings that do not support a strong link between such exposure and the development of psychopathology (Galea and colleagues as quoted in Bodas, Siman-Tov, Peleg, & Solomon, 2015).…”
Section: The Mediamentioning
confidence: 95%
“…are determined according to the symbol, which emancipate from the agent and are the real personality. Bodas et al (2015) research on effects of negative television contents on Israelis, the results showed that televised traumatic content and negative perception of broadcasts are directly associated increase of anxiety and psychopathology issues.…”
Section: Human Memory: Professionals' Perspectivesmentioning
confidence: 99%